Penerapan Metode Fuzzy Mamdani dan Metode Fuzzy Sugeno dalam Penentuan Jumlah Produksi (Unnes Journal of Mathematics, 2022)
This study examines the application of the Mamdani fuzzy method and Sugeno fuzzy method in determining the amount of jenang production, based on the variables of demand, supply, raw materials and production. The purpose of this study was to apply the Mamdani fuzzy and Sugeno fuzzy methods, and to find out which method is more accurate between the two methods in determining the amount of jenang production based on the MAPE value. Data collection was obtained at PJ Menara Kudus with Jenang Kombinasi and Jenang Wijen products in January 2020 to March 2021. The results of data processing obtained MAPE values for jenang kombinasi products using the Mamdani fuzzy method is 7,5% while the Sugeno fuzzy method is 7,1%, and the MAPE value for jenang wijen product using Mamdani fuzzy method is 21,7% while the Sugeno fuzzy method is 8,2%. Based on the result obtained, the MAPE value of Sugeno fuzzy method is less than Mamdani fuzzy method. So it can be concluded that Sugeno fuzzy method more accurate than Mamdani fuzzy method in determining the amount of jenang production at PJ Menara Kudus.